Genetic Algorithm Application for Hydrometer Tests - OZGAN, ERCAN; OZTURK, ALI (Asian Journal of Chemistry, 2010)
In this study, the results of the hydrometer tests were analyzed with statistical method and optimized by using genetic algorithms. For hydrometer tests; 0, 10, 20, 30, 40, 50 and 60 g sodium hexametaphosphate was respectively added into the prepared suspension. The specific gravity, pH and the conductivity were measured for each solution. As pointed out in the Turkish Standard (TS 1900), the soil' grain diameter in the suspension prepared with 40 g sodium hexametaphosphate was taken into consideration as reference. As a result, it was determined that the soil' average grain diameter in suspension added 0 g sodium hexametaphosphate was bigger 4.515 times than the reference grain diameter. When respectively added 10 g sodium hexametaphosphate in the suspension, the soil' average grain diameter bigger was 3.907 times than the reference grain diameter, when 20 g was added. It was 3.463 times bigger and in adding it was 30 g 2.119 times bigger. Besides, the hydrometer reading could only be done at 260 min when 50 g sodium hexametaphosphate was added in to the suspension. Moreover, the hydrometer couldn't be read in the suspension prepared with 60 g sodium hexametaphosphate. The obtained data were analyzed statistically by using SPSS programme and the experimental results were optimized by using genetic algorithms.